The Role of Sharia Economic Law in Supporting A Healthy Economic System for Indonesian Communities - Zahid Hasan; Abid Nurhuda (Bukhori: Kajian Ekonomi dan Keuangan Islam, 2023)
Purpose: The purpose of this research is to describe the Role of Sharia Economic Law in Supporting a Healthy Economic System for Indonesian Society. Methodology: The method used is literature study, then the data is collected using a qualitative approach, then the truth and validity are analyzed and the last is concluded descriptively. Results: The results of the study show that the Role of Sharia Economic Law in Supporting a Healthy Economic System for Indonesian Communities includes making people aware of the importance of paying Zakat, supporting the Prohibition of usury, fostering expectations of economic cooperation, supporting the social security system, supporting the prohibition of business practices which is dirty, and supports the supervision of the sharia economy in the state order so that all of these roles are following the maqosidu sharia which has been established by Islamic teachings. Limitations: This research only discusses some of the roles of sharia economic law and not all of them are mentioned, it is hoped that later there will be further research that will complement it. Contribution: This research is expected to be useful both for the authors themselves and for readers in general so that they can implement and support a sharia economic system in everyday life.